Effect of Giving Organic Fertilizer from Coffee Skin Waste With Soil and Bokashi on the Growth of Red Chilli - Al Hadi, Muhammad Ubaidillah; Chusnah, Miftachul; Hartanti, Dyah Ayu Sri; Aminatus Zuhria, Siti; Faizah, Mazidatul (AGARICUS: Advances Agriculture Science & Farming, 2024)
Organic fertilizer is natural fertilizer that can be obtained directly from nature, for example natural phosphate, manure, green manure and compost. Organic fertilizer can be said to be natural fertilizer because it is the result of the decomposition process of living material, such as plant, animal or other by-products. This research aims to determine the effect of using organic fertilizer, mixed with coffee skin waste, on the growth of chili stems and also the number of leaves on chili plants. The research method used in this research is quantitative descriptive research using the RAL (Completely Randomized Design) method on the growth of red chili plants. The results of this research show that there are significant changes in chili plants that use organic fertilizer mixed with coffee skin waste, and in chili plants without fertilizer. The results of variance testing showed Fhit 15 and 20 in plant height growth, while for number of leaves Fhit was 560992 and 63438 in a period of 10 days.